Analysis of English Tenses in the Introduction Sections of Artificial Intelligence Research Articles in Top Computer Science Journals from the SCImago Journal Rank and the Country Rank - Noksub, Siriwimon; Kumpipot, Piyatida (Journal of Humanities and Social Sciences Nakhon Pathom Rajabhat University, 2026)
Objective of this study was to identify tenses in English occurred in the actual amount of 43 introduction sections of research articles in the field of computer science published in 2023 in a journal which was chosen based on the highest index from Scimago & Country Rank from 2022 to 2023. The concepts and sources about tenses were adapted from Abusch (1988), Britannica (2023: online), and Nabilversity (2023: online)’s study, which was used as a set of codes to identify tenses in English. The findings showed that the most frequently used tense was Present Simple Tense as 90.93% or 2,226 times, followed by Present Perfect Tense was used as 5.56% or 136 times and Past Simple Tense as 3.23% or 79 times. The least frequently used tenses were Present Continuous Tense as 0.16% or 4 times and Future Simple Tense as 0.12% or 3 times.